Analysis of the application of additional correction methods of insufficient adherence to treatment in patients with resistant and pseudo-resistant arterial hypertension - Zbitnieva, V. (Journal of Education, Health and Sport, 2017)
The article considers the results of the use of home blood pressure monitoring and telephone consultations (visits) on the background of the optimization of antihypertensive therapy in patients with resistant and pseudo-resistant arterial hypertension.